ECOLOGICAL RESTORATION TECHNIQUES FOR COASTAL ECOSYSTEMS AFFECTED BY HUMAN ACTIVITIES - Donny Juliandri Prihadi; Yovita Yovita; Aiman Fariq; Iriana Bakti (Yayasan Adra Karima Hubbi, 2025)
Coastal ecosystems are increasingly threatened by human activities, including urbanization, pollution, and climate change. These disturbances have led to significant biodiversity loss and degradation of ecosystem services. Understanding effective restoration techniques is essential for reversing these negative impacts and promoting ecological resilience. This study aims to evaluate various ecological restoration techniques applicable to coastal ecosystems affected by human activities. By assessing the effectiveness of these techniques, the research seeks to identify best practices for restoring ecological integrity and enhancing biodiversity. A comprehensive literature review was conducted, focusing on case studies of restoration projects in coastal areas. Techniques evaluated included habitat restoration, species reintroduction, and the implementation of sustainable management practices. Data on ecological outcomes, species diversity, and community structure were analyzed. Findings indicate that a combination of techniques, such as habitat restoration and community engagement, significantly enhances the recovery of coastal ecosystems. Successful case studies demonstrated improvements in biodiversity and ecosystem function, highlighting the importance of adaptive management strategies tailored to specific environmental contexts. This research underscores the critical need for effective ecological restoration techniques in coastal ecosystems impacted by human activities.